Between Hopes and Threats: New Migratory Birds Records on the Sawala Mandapa Education and Training Forest, Indonesia - Dian Iswandaru; Gugie Nugraha; Aris Djati Dwi Iswanto; Yulia Rahma Fitriana; Kornelia Webliana (Forestry Faculty, Universitas Hasanuddin, 2022)
Java Island is one of the tropical areas for bird migration, especially the Asian-Australian flyway of migratory birds. The SMETF is one of the protected forest areas that migratory birds can visit in Java. This research aims to identify migratory birds in SMETF. Transect and point count methods are used to observe migratory bird movements and their activities. In the research area, four migratory birds were identified: Ficedula zanthopygia, Agropsar sturninus, Pernis ptilorhynchus o., and Accipiter soloensis. The first and second species showed many activities for four months from October 2020 to January 2021, and this is an indication that both are using the research site as a wintering habitat. The activities of the Pernis ptilorhynchus o., Accipiter soloensis were dominated by flying “flock” over the forest. Only the Pernis ptilorhynchus was observed carrying out hunting activities, indicating that this bird uses the area as a stopover area. This research also identified illegal hunting techniques, such as ngaleugeut and mikat, as severe threats to migratory birds in the SMETF.